2006
DOI: 10.1007/s00109-006-0100-2
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant intestinal expression and allelic variants of mucin genes associated with inflammatory bowel disease

Abstract: Loss of intestinal mucosa integrity is an important factor in the pathogenesis of inflammatory bowel disease (IBD). The aim of this study was to characterize expression changes and allelic variants of genes related to intestinal epithelial barrier function in this disease. Therefore, ileal and colonic mucosal biopsies from nonaffected regions of patients with ulcerative colitis (UC) and Crohn's disease (CD), as well as non-IBD probands, were subjected to Affymetrix DNA-microarray analysis. Real-time reverse tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
5
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 44 publications
6
111
5
11
Order By: Relevance
“…Moehle et al (25) found that MUC1 was highly expressed in adult prostate, mammary glands, trachea, lung, small intestine, colon, and in fetal lung. Chen and colleagues (26) generated recombinant adenoviral vectors containing the 5' flanking region of the MUC1/DF3 promoter (-725 to +31), expressing the LacZ gene (Ad.DF3ß-gal) or the herpes simplex virus thymidine kinase (HSV-tk) gene (Ad.Df3-tk).…”
Section: Tissue-specific Promoter Systemsmentioning
confidence: 99%
“…Moehle et al (25) found that MUC1 was highly expressed in adult prostate, mammary glands, trachea, lung, small intestine, colon, and in fetal lung. Chen and colleagues (26) generated recombinant adenoviral vectors containing the 5' flanking region of the MUC1/DF3 promoter (-725 to +31), expressing the LacZ gene (Ad.DF3ß-gal) or the herpes simplex virus thymidine kinase (HSV-tk) gene (Ad.Df3-tk).…”
Section: Tissue-specific Promoter Systemsmentioning
confidence: 99%
“…У людини ідентифіковано 21 muc ген. У осіб із виразковим колітом вста-новлено пригнічення експресії гена muc12 [71].…”
Section: бактерії слизової оболонки товстого кишечникаunclassified
“…Відомі та-кож інші джерела сульфату в кишечнику, зокрема сульфатвмісні полісахариди (хондроїтин сульфат) [39]. Як уже згадувалося, муцин кишечника також є сульфат-вмісною сполукою [71]. Бактерії роду Clostridium, Bifidobacterium, а також Bacteroides fragilis можуть розщеплювати муцин, у результаті чого утворюється доступ-ний для СВБ сульфат [39,62].…”
Section: шляхи метаболізму воднюunclassified
“…De plus, l'utilisation de puces à ADN a révélé une diminution de l'expression des gènes codant les mucines dans l'iléon et le côlon des patients [6]. La cohésion et l'étanchéité de la muqueuse intestinale sont assurées par les jonctions cellulaires des cellules épithéliales de l'intestin.…”
Section: Données Génétiques Et Gènes De Susceptibilitéunclassified